Minority stress, intra-minority stress and social anxiety: Examining an extended psychological mediation framework among sexual minority men. (13th November 2019) - Mahon, C; Kiernan, G; Gallagher, P
Abstract: Background: Compared to their heterosexual counterparts, sexual minority men (SMM) are at an increased risk of social anxiety disorder. Distal (i.e., everyday discrimination) and proximal (i.e., internalised homophobia, rejection sensitivity, concealment of sexual orientation) minority stress processes are associated with heightened social anxiety for SMM. Stressors emerging from within the sexual minority male community, termed intra-minority stress, and psychological processes that may foster resilience (i.e., a sense of coherence, connectedness to the LGBT community) are less explored in this area. This study examined potential pathways between everyday discrimination, intra-minority stress, proximal minority stressors, resilience and social anxiety. Methods: Self-identified SMM (N = 255) residing in the Republic of Ireland completed an online survey containing measures of minority stress, intra-minority stress, resilience and social anxiety. Structural equation modelling was used to examine the model. Results: The model yielded a good fit to the data, X2(16) = 26.61, CFI = .99, TLI = .97, RMSEA = .05, and SRMR = .03. Rejection sensitivity and a sense of coherence had a significant indirect effect in the relationships between both exogenous variables (i.e., discrimination and intra-minority stress) and social anxiety. There were no significant pathways to social anxiety involving concealment of sexual orientation, internalised homophobia or LGBT community connectedness. Conclusions: For SMM, minority stress processes and intra-minority stress are important determinants of social anxiety. Our findings demonstrate that proximal minority stressors may operate differently in a social anxiety context for SMM in western European countries. A sense of coherence was an integral factor in the model and demonstrated the strongest association with social anxiety.